Grammatical Errors in Students’ Recount Text Writing (A Case Study in The Third Grade of SMAN 22 Jakarta) - Pamellia Ayu Ariansyah; Dwi Rahayu (Proceedings Series on Social Sciences & Humanities, 2024)
This study is aimed to find out grammatical errors and the sources of errors in students’ recount texts. The subject of this study is the third-grade students of SMAN 22 Jakarta in the academic year 2023/2024 which consists of 23 students. Specifically, their recount texts focused on recounting their vacation activities. From the entire third-grade class of 23 students, 16 students were selected as the study sample using the purposive sampling technique. This study used a qualitative approach to analyze and identify grammatical errors. The analysis was carried out by referring to Dulay, Burt & Krashen’s theory, a surface strategy taxonomy consisting of Omission, Addition, Misformation, and Misordering and the sources of errors based on Ellis’s theory are Interlingual Transfer and Intralingual Transfer. The result of this study showed that the total number of grammatical errors made by the students in their recount texts is 32 errors. Which consist of 4 omission errors, 7 addition errors, 8 misordering erros, and 13 misinformation errors. Accordingly, the most frequent error is misinformation error which corresponds to 13 (40,6%) of the total error. Furthermore, this study also revealed that most of the errors are caused by Intralingual Transfer (30 errors or 94% of the total error). Based on these findings, it concluded that the students had some difficulties in applying English grammar rules in their writings. Therefore, it is suggested to be aware and pay more attention to improve the English teaching and learning process.